Exploring the Socio-Economic Impact of Microfinance in Rural Nepal: A Qualitative Study of Beneficiaries’ Experiences - Bhatta, Dharma Dev; Priya, Ashutosh (AMC Journal (Dhangadhi), 2025)
Microfinance is increasingly recognized as a financial tool for addressing poverty and fostering socio-economic development, particularly in low- and middle-income countries (LMICs), including Nepal. This study examines the multi-dimensional impact of microfinance programs on income stability, livelihood diversification, education, health, and women’s empowerment, focusing on three districts: Kailali, Banke, and Dhanusha. This study employed a qualitative research design to analyze the impact of microfinance programs on income, livelihoods, education, health, and empowerment in rural Nepal. A total of three FGDs were conducted with eight participants in each group, and 15 participants were chosen for in-depth qualitative interviews. Findings reveal that microfinance significantly improved household income, facilitated small business growth, and enhanced access to education and healthcare. Furthermore, women’s participation in microfinance programs increased decision-making power and community engagement, underscoring its role in social transformation. However, challenges like repayment stress, over-indebtedness, and limited outreach persist, highlighting the need for tailored products, integrated support services, and improved outreach strategies. The study concludes that while microfinance has transformative potential, addressing these barriers is crucial for achieving inclusive and sustainable rural development in Nepal.